Characterization of Mn0.67Zn0.33Fe2O4 nanoparticles synthesized under different ph - Ichikawa, Rodrigo Uchida; Yoshito, Walter Kenji; Saeki, Margarida Juri [UNESP]; Maranhão, Willian C. A.; Goulart, Fátima; Martinez, Luis Gallego (Trans Tech Publications, 2017)
Nanostructured Mn-Zn ferrites were synthesized using co-precipitation in alkaline solution with different pH. The samples were characterized using X-ray diffraction (XRD), X-ray fluorescence (XRF), thermal analysis (TG-DTA), dynamic light scattering (DLS) and scanning electron microscopy (SEM) techniques. Monophasic nanoparticles were formed when synthesized with pH 10.5. This sample was heat-treated and its XRD data was refined by the Rietveld method. Mean crystallite sizes and microstrains were determined from X-ray line profile analysis using Single-Line and Warren-Averbach methods, which revealed a mean crystallite size of approximately 10 nm and negligible microstrains. Zn content was estimated using refined cell parameters, giving a value of 33 at %, in accordance with XRF result. TG-DTA revealed that the incorporation of α-Fe2O3 occurs around 1130 °C and 1200 °C with recrystallization of the Mn-Zn ferrite spinel phase. DLS showed that mean particle size increase with temperature up to 1159 nm at 800 °C. SEM analysis showed the samples agglomerate and present similar morphology with negligible size changing when calcined between 280 °C and 800 °C. However, the sample calcined at 1200 °C presents larger agglomerates due to the sintering process.
Keywords: Dynamic light scattering; Mn-Zn ferrite nanoparticles; Scanning electron microscopy; Thermal analysis; X-ray diffraction; X-ray fluorescence